PENGGUNAAN PERKEMBANGAN APLIKASI FACEBOOK BAGI REMAJA DI DESA TINIAWANGKO MINAHASA SELATAN (JURNAL PARADIGMA : Journal of Sociology Research and Education, 2021)
The purpose of this research is to analyze and describe how the use of facebook application development for teenagers in Tiniawangko village south minahasa The research method used is qualitative Qualitative research methods aim to provide a systematic factual and accurate description Data collection techniques are observation interviews and documentation The results of research in the field show that the use of Facebook application development for teenagers in Tiniawangko village is very important because it can help teenagers to add insight knowledge interact be creative and can also find out the latest information and can communicate with friends and family< p>
Keywords: Development; Facebook Application; For Teens